2002
DOI: 10.1063/1.1447181
|View full text |Cite
|
Sign up to set email alerts
|

Magnetization reversal in exchange biased Co/CoO probed with anisotropic magnetoresistance

Abstract: The magnetization reversal in exchange coupled polycrystalline Co/CoO bilayers has been investigated as a function of CoO thickness using anisotropic magnetoresistance as a probe. The anisotropic magnetoresistance (AMR) was measured during the magnetization reversal and it was used to determine the orientation of the magnetization. For thin CoO layers large training effects were present; ergo the first hysteresis loop after field cooling was not the same as the second. The magnitude of the observed training wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

10
58
0

Year Published

2003
2003
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 67 publications
(68 citation statements)
references
References 10 publications
10
58
0
Order By: Relevance
“…These data show that the reversal process is coherent rotation of magnetization in the uniaxial anisotropy field of approximately 20 Oe. In the easy-axis minor loop, resistance remains nearly constant, consistent with reversal by propagation of a small number of domain walls [22]. Fig.…”
mentioning
confidence: 49%
See 1 more Smart Citation
“…These data show that the reversal process is coherent rotation of magnetization in the uniaxial anisotropy field of approximately 20 Oe. In the easy-axis minor loop, resistance remains nearly constant, consistent with reversal by propagation of a small number of domain walls [22]. Fig.…”
mentioning
confidence: 49%
“…Due to AMR, the resistance of a Py film, R, depends on the angle, θ, between the directions of current and magnetization: R = R 0 + ∆Rcos 2 (θ). Since ∆R > 0 for Py, higher resistance corresponds to a greater fraction of magnetization parallel to the current direction [22]. Figures 1 (a) and (b) show resistance of a Py(6)/Nb(23)/Py(6)/Ir 25 Mn 75 (10) spin valve at T = 4.2 K (T > T c ) as a function of magnetic field applied in the plane of the sample parallel (easy axis) and perpendicular (hard axis) to the current direction.…”
mentioning
confidence: 99%
“…4 However, it has been reported that thin CoO films with low magnetocrystalline anisotropy can have large rotatable anisotropy. 36,43 As mentioned above, the classification of the interface UCSs has been recently examined, 23 and it has been demonstrated that although highly anisotropic, an UCS can contribute to H C and not to H EB if it is strongly coupled to the adjacent FM. Conversely, a low-anisotropy UCS will add to EB if the coupling to the FM is sufficiently weak.…”
Section: Resultsmentioning
confidence: 99%
“…Usually, jH EB j increases with the AFM thickness in this regime with low AFM layer thickness. 36 Moreover, it should also be taken into account that although our sample was grown in a similar fashion, the bilayers of Gruyters were grown on top of Si(111) substrates with hydrogen passivation, while our sample was deposited on top of a thermally-oxidized Si(100) substrate which was covered with a 10 nm thick Au buffer layer. Moreover, the blocking temperature of the samples of Gruyters is around 175 K, whereas the blocking temperature of our CoO layer is 125 K, suggesting that the formed CoO might be more hyperstoichiometric with a higher degree of polycrystallinity, i.e., more prone to nanostructuring effects.…”
Section: Resultsmentioning
confidence: 99%
“…Many experimental and theoretical studies have shown that the existence of domains in the AF layer is necessary for the appearance of exchange bias in FM/AF bilayers. [3][4][5][6][7][8][9][10][11][12][13][14][15][16][17] Theoretical models have suggested both parallel and perpendicular domain walls. Mauri et al 3 suggested that a domain wall forms in the AF layer parallel to the interface while the magnetization of the FM layer rotates.…”
mentioning
confidence: 99%